2001
DOI: 10.1099/0022-1317-82-1-25
|View full text |Cite
|
Sign up to set email alerts
|

RNAs 1 and 2 of Alfalfa mosaic virus, expressed in transgenic plants, start to replicate only after infection of the plants with RNA 3

Abstract: The genome of Alfalfa mosaic virus (AMV) is divided among three plus-strand RNAs which are separately encapsidated. The RNA 1-encoded P1 protein with putative methyltransferase and helicase activity and the RNA 2-encoded P2 protein containing the GDD motif of viral plus-strand RNA polymerases have been identified as subunits of the purified AMV RNA-dependent RNA polymerase complex (RdRp ; Quadt et al., 1991). The P3 protein encoded by RNA 3 is involved in virus movement, and the subgenomic RNA 4, which is synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…As in R12 plants, the accumulation of plus-strand RNA 1 and 2 could then be the result of protection of the Pol II transcripts from degradation after minusstrand synthesis or of transcription of plus strands by the AMV RdRp on the minus-strand templates (49). In both cases, plusstrand accumulation would be dependent on and coincide with minus-strand accumulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in R12 plants, the accumulation of plus-strand RNA 1 and 2 could then be the result of protection of the Pol II transcripts from degradation after minusstrand synthesis or of transcription of plus strands by the AMV RdRp on the minus-strand templates (49). In both cases, plusstrand accumulation would be dependent on and coincide with minus-strand accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…However, when RNAs 1 and 2 are expressed from the 35S promoter in transgenic plants (R12 plants), CP is not required for minus-strand RNA synthesis (49). It was proposed that the poly(A) tail of the nuclear AMV transcripts may compensate for a putative role of CP in translation of the inoculum RNAs (49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1, sequences with apparent similarity to the SIN Pro180-Thr-X-Arg-Ser184 nsP4 sequence also have upstream sequences rich in Lys and other basic amino acids. The SIN nsP4 Arg183 region did not resemble the ilarvirus and alfalfamovirus coat protein motif's role in plus-strand synthesis (50). The Arg residue in the poliovirus VPg sequence is proposed to stabilize a UTP moiety for transfer to the terminal Tyr residue of VPg (30) and to function during plus-and minus-strand initiation (14,32).…”
Section: Discussionmentioning
confidence: 99%
“…CP is required to initiate minus-strand RNA synthesis in protoplasts inoculated with T7 RNA polymerase transcripts corresponding to the genomic RNAs (18). However, CP is not required to initiate minus-strand RNA synthesis when the genomic RNAs are expressed from cDNAs flanked by the cauliflower mosaic virus 35S promoter and nopaline synthase terminator from nuclear transgenes in transgenic plants (19,20), from a T-DNA vector in agroinfiltrated leaves (21), or from plasmids used to inoculate plants (22). We have suggested that in a natural infection, CP is required in a step before the initiation of AMV minus-strand RNA synthesis, probably the translation of the viral RNAs (15, 18).…”
mentioning
confidence: 99%